Rifle and aiming point accelerations do not differ between the most and least accurate shots in biathlon shooting within an athlete - Köykkä Miika; Linnamo Vesa; Ruotsalainen Keijo; Rantalainen Timo; Laaksonen Marko S. (Sciendo, 2023)
Study aim: As studies from shooting disciplines other than biathlon have observed associations between weapon accelerations and shooting performance, this study investigated whether accelerations of the rifle stock and aiming point (the point on the target where the rifle is aimed at) are associated with shooting performance, and differences in rifle and aiming point accelerations between the most and least accurate shots. Further, associations between rifle and aiming point accelerations were studied.